ANSWER TO COMMENT BY RENÉ CABRAL - Moreno Brid, Juan Carlos; Krozer, Alice (Investigación Económica, 2016)
We thank René Cabral for his comments and suggestions on our paper Inequality and minimum wage policy: Not even talking, much less walking in Mexico (2015). It seems to us that although Cabral does identify some omissions in our paper, in general terms he agrees with most of our main conclusions. These are that the high inequality in Mexico is socially and economically inefficient; that it is indispensable to further study the links between inequality and minimum wages in Mexico; that this relationship, as well as the very low levels of minimum wages in Mexico, might have something to do with the less-than-optimal growth records of recent decades; that the chances for the legal delinking (desvinculación) of minimum wages to other non-labor related variables as well as the implementation of a new policy to increase them in a significant and sustainable way in the country ―fiercely opposed by some sectors of the Mexican elite― will depend to a large extent on politics...